2015
DOI: 10.1111/jphp.12484
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin inhibits inflammation and attenuates myocardial ischaemic injury by aryl hydrocarbon receptor

Abstract: Our findings extend the list of AhR ligands beyond exogenous toxins and endogenous molecules to cardiac immunological factors, and moreover it could be considered potential drug targets due to its pathological modulatory properties, while baicalin demonstrated promise as a novel vehicle for ischaemic heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…Therefore, cytokines expression and neutrophil infiltration are central mediators of inflammation. On the other hand, previous evidence showed that baicalin inhibited inflammatory responses via down-regulation of cytokines in an animal model with myocardial ischemic injury [26]. Another report also showed that baicalin suppressed the production of cytokines and leukocyte migration in in vitro and in vivo studies [27].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, cytokines expression and neutrophil infiltration are central mediators of inflammation. On the other hand, previous evidence showed that baicalin inhibited inflammatory responses via down-regulation of cytokines in an animal model with myocardial ischemic injury [26]. Another report also showed that baicalin suppressed the production of cytokines and leukocyte migration in in vitro and in vivo studies [27].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Baicalin was reported to ameliorate isoproterenol‐triggered acute myocardial infarction by suppressing inducible nitric oxide synthase, oxidative stress, inflammation, and P38MAPK pathway in rat (Sun, Wu, Song, & Li, ). Besides that, Xue et al reported that Baicalin attenuated myocardial ischemic damage by suppressing the inflammatory response via devitalizing the aryl hydrocarbon receptor (Xue et al, ). However, the effect of Baicalin on myocarditis has not been studied thoroughly.…”
Section: Introductionmentioning
confidence: 99%
“…baicalensis is mainly distributed in East Asia and its dry roots were prevalently used to treat inflammatory and bacterial diseases as old-line China traditional medicine (Yamamoto, 1991;Huang et al, 2012;Xue et al, 2015). In present study, the bioinformatic analyses of 4cl family from S. baicalensis were completed, which would pave for further studies of physichemical properties of 4CL protein family and its related molecular mechanism of flavonoid biosynthesis.…”
Section: Fig 1 Flavonoid Biosynthetic Pathway In Scutellaria Cellsmentioning
confidence: 93%